Modelling of Adaptation Strategies for Different Entities; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 7 : Lifelong Wellbeing in the World (WELLSO 2015) - Berestneva O. G. Olga Grigorievna; Marukhina O. V. Olga Vladimirovna; Ivankina L. I. Lyubov Ivanovna; Shukharev S. O. (2016, 2016)
Title screen